2010
DOI: 10.1016/j.jinf.2010.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial translocation across ePTFE vascular graft surfaces

Abstract: Summary Objectives Vascular graft infections arise from bacterial colonization of either the external or internal graft surfaces. We assessed whether methicillin-resistant Staphylococcus aureus (MRSA) and Escherichia coli could translocate through pores of ePTFE grafts. Methods To assess translocation from the internal to the external surface, we placed 105 cfu of bacterial suspension inside ePTFE graft segments and suspended them in sterile broth for 72 h. To assess translocation from the external to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…15,16 However, numerous clinical reports showed that bacterial infection is one of the most common complications after biomaterial implantation, and the underlying mechanism is mainly due to sustained secretion of inflammatory factors and reduction in the ability of local tissue cells to remove bacteria after long-term use. 17,18 More importantly, the formation of biofilm on a biomaterial surface by bacterial adhesion has strong drug resistance and resistance to phagocytosis. Current studies show that modifications by covering with a bioactive factor or biomaterial surfaces prevascularized in vitro exhibit a low bacterial adhesion rate, improving the antiinfection ability of implanted materials.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 However, numerous clinical reports showed that bacterial infection is one of the most common complications after biomaterial implantation, and the underlying mechanism is mainly due to sustained secretion of inflammatory factors and reduction in the ability of local tissue cells to remove bacteria after long-term use. 17,18 More importantly, the formation of biofilm on a biomaterial surface by bacterial adhesion has strong drug resistance and resistance to phagocytosis. Current studies show that modifications by covering with a bioactive factor or biomaterial surfaces prevascularized in vitro exhibit a low bacterial adhesion rate, improving the antiinfection ability of implanted materials.…”
Section: Discussionmentioning
confidence: 99%
“…In surgery for MTAA, expanded polytetrafluoroethylene (ePTFE) grafts and RFP-soaked ePTFE grafts have been used, and there are reports on such usage. Narasimhan et al reported that ePTFE graft did not allow methicillin-resistant Staphylococcus aureus (MRSA) and E. coli to pass through the vessel wall, even when their biofilm was formed on the vessel surface (Narasimhan et al 2010 ). As far as our research is concerned, there were no reports of increased postsurgical infections between the use of ePTFE graft and non ePTFE grafts (Taichi et al 2016 ; Hai Lei and Yui Che 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…79 Although it is believed that the translocation of bacterial cells along the pores of the graft has an important role in infection, methicillin-resistant Staphylococcus aureus and Escherichia coli do not exhibit such a behavior. 80…”
Section: Cardiac Implantsmentioning
confidence: 99%